HUBUNGAN KONSUMSI KALSIUM DALAM MAKANAN DAN MINUMAN DENGAN KEPARAHAN KARIES GIGI PADA MURID KELAS IV DAN V SDN MLATI KIDUL 1 DAN 2 KUDUS - Wulandari Meikawati; Sayono -; Ulfa Nurullita (JURNAL LITBANG, 2005)
Oral health hygiene constitutes one of public health problems that require comprehensive management due to its wide dimension. The lack of Calcium will hinder the process of teeth calcification and slow down the dental maturity. Low dental quality will lead the dental carries. Calcium is highest number of mineral in the human body. It will be obtained only from food, and the lack of it in the body will cause dental carries. This research is an explanatory research with survey method and cross sectional approach. The total number of respondents is one hundred (100) students of grade 4 and 5 in the elementary school. The variables of the research include calcium intake during 3 x 24 hours, the frequency of eating high calcium food, frequency of eating carriogenic food, frequency, of tooth brushing, and the severity of the dental carries. The result of the research shows all ,students .suffer the deficiency of calcium (97% severaly lack of calcium, 1% moderately lack of calciurn, and 2 % lack of the calcium). Most of the students (40%) suffer dental carries of tight level. The result of rank Spearman test shows there is not correlation between calcium intake and food and beverage and the severity of dental carries (p=0,185). There is no correlation between frequency of eating high calcium food and the severity of dental carries (p=0,527). There is no correlation between frequency of tooth brushing and the severity of dental carries (p=0,495). Keyword : calcium intake, frequency of tooth brushing, severity of the dental carries